2021
DOI: 10.1021/acs.jced.1c00328
|View full text |Cite
|
Sign up to set email alerts
|

Speed of Sound in Helium-4 from Ab Initio Acoustic Virial Coefficients

Abstract: We present values for 4He of temperature-dependent acoustic virial coefficients that appear in series expansions for the speed of sound in the gas (AVEOS). Coefficients are computed from first-principles molecular models from the literature and are presented for expansions both in density and in pressure. These coefficients, labeled here as Ω n and ω n , respectively, are determined from previously reported values of the pressure virials B n as a function of temperature T. Data are provided for T from 2.6 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(19 citation statements)
references
References 73 publications
(198 reference statements)
3
16
0
Order By: Relevance
“…The virial EOS leads in turn to a similar power-series expansion for the “acoustic compressibility factor” Z a as follows Z normala = ( M c 2 γ 0 R T ) = 1 + normalΩ 2 ρ + normalΩ 3 ρ 2 + normalΩ 4 ρ 3 + · · · Here, γ 0 = 5/3, and Ω n is the n th acoustic virial coefficient, which is related to the corresponding, and all lower order, ordinary virial coefficients B n and their first two temperature derivatives. The EOS in this form has been studied in detail by Gokul et al on the basis of the ab initio pair potential of Przybytek et al , and the non-additive three-body correction of Cencek et al Gokul et al present precise calculations of the acoustic virial coefficient up to order n = 7, estimates of the statistical uncertainty of each coefficient, and correlations of both B n and Ω n as functions of temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The virial EOS leads in turn to a similar power-series expansion for the “acoustic compressibility factor” Z a as follows Z normala = ( M c 2 γ 0 R T ) = 1 + normalΩ 2 ρ + normalΩ 3 ρ 2 + normalΩ 4 ρ 3 + · · · Here, γ 0 = 5/3, and Ω n is the n th acoustic virial coefficient, which is related to the corresponding, and all lower order, ordinary virial coefficients B n and their first two temperature derivatives. The EOS in this form has been studied in detail by Gokul et al on the basis of the ab initio pair potential of Przybytek et al , and the non-additive three-body correction of Cencek et al Gokul et al present precise calculations of the acoustic virial coefficient up to order n = 7, estimates of the statistical uncertainty of each coefficient, and correlations of both B n and Ω n as functions of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Here, γ 0 = 5/3, and Ω n is the n th acoustic virial coefficient, which is related to the corresponding, and all lower order, ordinary virial coefficients B n and their first two temperature derivatives. The EOS in this form has been studied in detail by Gokul et al 41 on the basis of the ab initio pair potential of Przybytek et al 42,43 and the non-additive three-body correction of Cencek et al 44 Gokul et al 41 present precise calculations of the acoustic virial coefficient up to order n = 7, estimates of the To apply this EOS, we first solved eq 8 for the molar density corresponding to the experimental temperatures and pressure and then used eq 9 to evaluate the speed of sound using, in both equations, coefficients up to n = 7 as correlated by Gokul et al 41 We did not make use of the pressure-series expansion of Z a reported by Gokul et al 41 because it does not appear to converge at the highest pressures studied in this work. On the other hand, both eqs 8 and 9 appear to converge to this order to within 0.01%, as judged by the difference between truncation after n = 6 and after n = 7.…”
Section: Comparison With Data From Ab Initio Acoustic Virial Coeffici...mentioning
confidence: 99%
“…The virial equation of state (VEOS) describes the thermodynamic properties of fluids in terms of a power series in a state variable, most commonly the density. Specifically, the pressure P is given by P k normalB T = prefix∑ n = 1 B n ( T ) ρ n where T is the temperature, k B is the Boltzmann constant, and ρ ≡ N / V is the number density, with N being the number of molecules and V is the volume; according to the ideal-gas law, B 1 ≡ 1. The VEOS is an appealing framework for representing properties because the coefficients that appear in the equation, the virial coefficients, B n ( T ), can be computed rigorously from molecular models or even first-principles methods. Other thermodynamic properties can be computed from the VEOS using standard thermodynamic manipulations, in some cases requiring temperature derivatives of the B n . The primary disadvantage of the VEOS as commonly formulated is that the power series is not convergent, or not quickly convergent, at some conditions of interest, and in particular, it is not applicable to condensed phases at all.…”
Section: Introductionmentioning
confidence: 99%
“…Jäger et al showed that their VEOS7 for the noble gas argon obtained from ab initio two-body and nonadditive three-body potentials is nearly as accurate as the best experimental data at those densities at which the virial expansion is sufficiently converged. Virial coefficients of the noble gas helium have been calculated with extremely low uncertainties by several research groups (see ref and references therein), resulting in a VEOS7 that, when converged, has an accuracy that cannot be attained by any existing experimental technique. Although our VEOS8 for carbon dioxide obtained from fine-tuned ab initio two-body and nonadditive three-body potentials cannot match the accuracy of the best experimental data, the agreement with experiment is still very satisfactory.…”
Section: Introductionmentioning
confidence: 99%